DETERMINATION OF PERMANENT LECTURERS IN IBM ASMI INFORMATION SYSTEM PRODUCT WITH SAW AND CURRENT METHOD - Rendi Septian; Istiqal Hadi; Ridwansyah Ridwansyah; Windu Gata; Widiastuti Widiastuti; Muhammad Iqbal (LPPM Nusa Mandiri, 2021)
Abstract— Determining the quality standards of lecturers refers to the criteria of education, research, and community service. The campus can carry out the first process for selecting permanent lecturers effectively by looking at several criteria. By using a Decision Support System (DSS), the four categories can be used as guidelines for decision-makers to choose permanent lecturers. The goal of writing this journal is to support the effectiveness of the time for decision-makers to choose permanent lecturers in the early stages by combining the Additive Ratio Assessment (ARAS) and Simple Additive Weighting (SAW) methods. Where the SAW method has the advantage of accurate assessment because the value of criteria and weights have been determined, while the ARAS method compares each criterion value to each optimal alternative as a whole to get an ideal alternative. The result of combining the two methods can describe the prospective lecturers who are suitable to be used as permanent lecturer criteria. Judging from the ranking results in calculations, the values obtained are 0.146341, 0.134146, and 0.121951. These results prove that ranking with an assessment using the combination of SAW and ARAS methods results in an effective, accurate, and efficient assessment. Keywords: Additive Ratio Assessment, Decision Support Systems, Permanent lecturer, Simple Additive Weighting. Intisari— Menentukan standar kualitas dosen mengacu kepada kriteria pendidikan, penelitian, dan pengabdian kepada masyarakat. Pihak kampus dapat melakukan proses pertama untuk pemilihan dosen tetap secara efektif dengan melihat beberapa kriteria. Dengan menggunakan Sistem Penunjang Keputusan (SPK), keempat kategori tersebut bisa dijadikan pedoman bagi pengambil keputusan untuk memilih dosen tetap. Tujuan penulisan jurnal ini adalah untuk membantu keefektifan waktu bagi pengambil keputusan untuk memilih dosen tetap tahap awal dengan penggabungan metodeAdditive Ratio Assessment (ARAS) dan Simple Additive Weighting (SAW).Dimana metode SAW mempunyai keunggulan penilaian akurat karena untuk nilai kriteria dan bobot telah ditentukan, sementara metode ARASmelakukan perbandingan setiap nilai kriteria terhadap masing alternatif optimal secara keseluruhan untuk mendapatkan alternatif yang ideal. Hasil penggabungan dua metode tersebut dapat menggambarkan calon dosen yang sesuai untuk dijadikan kriteria dosen tetap.Dilihat dari hasil perangkingan dalam perhitungan, nilai yang didapat 0,146341 ,0,134146 dan 0,121951. Hasil ini membuktikan bahwa perangkingan dengan penilaian menggunakan penggabungan metode SAW dan ARAS menghasilkan penilaian yang efektif, akurat dan efisien. Kata Kunci: Additive Ratio Assessment, Sistem Penunjang Keputusan, Dosen Tetap, Simple Additive Weighting.